Effects of different reduction patterns on stress distribution in patients with intertrochanteric fractures with intramedullary nail fixation: a finite element analysis - Zhu, Jiajing; Du, Zhipeng; Cao, Changpeng; Gao, Yang; Chen, Xinxiao; Xing, Haiyang; Wang, Gang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivePositive medial cortical support is a reliable fracture reduction pattern, but existing research on its use is mainly qualitative. We conducted this finite element analysis study to quantitatively evaluate the usefulness of positive cortical support for intertrochanteric fracture reduction.MethodsTwenty-five models of intramedullary nail fixation for AO type 31-A1.2 intertrochanteric fractures subjected to different reduction patterns were established. The peak von Mises stress at the femoral fracture surface, proximal intersection of the intramedullary nail, and distal intersection of the intramedullary nail, as well as the maximum fracture displacement, were determined by finite element analysis under the three working conditions of standing, walking, and walking stairs.ResultsAs the head–neck fragment moved forward, the von Mises stress at the fracture surface, the proximal intersection point of the intramedullary nail, and the distal intersection point gradually decreased. This resulted in reduced fracture displacement, a significant decrease in trabecular bone volume, and a slight increase in the risk of screw cut-out. As the head–neck fragment moved medially, the fracture gained positive support from the medial cortex, leading to a gradual decrease in von Mises stress at the fracture surface and the proximal intersection point of the intramedullary nail, as well as reduced fracture displacement. However, the von Mises stress at the distal intersection point gradually increased.ConclusionThe reduction pattern involving positive medial, anteromedial, and anterior cortical support may be an effective alternative to anatomical reduction for the treatment of difficult-to-reduce intertrochanteric fractures.